Fatigue Analysis of Catenary Mooring System due to Harsh Environment in Head Seas - Fuad Mahfud Assidiq; Daeng Paroka; Muhammad Zubair Muis Alie; Syerly Klara (EPI International Journal of Engineering, 2018)
The Floating Production Unit (FPU) is a floating gas production barge that is moored by catenary mooring system to the seabed. In the operation, Floating Production Unit (FPU) will get dynamic loads such as ocean waves, ocean currents, and winds on the mooring line structure periodically. This may cause damage to mooring line structures which effect to the operational structure performance. The aim of the present study is to discuss fatigue life on catenary mooring system. The model studied refers to the comparison of using or without using the Single Line Freestanding Riser (SLFR), the operational design and installation conditions at FPU Gendalo-Gehem and located in the Makassar Strait. The dimensions of mooring line type six-strand wire rope are 0,115 meters outer diameter and 1.200 meters length will be fatigue life analyzed. The FPU motion observation in heading 1800 (head seas) shows the highest Response Amplitude Operator (RAO) surge, sway, heave, roll, pitch, and yaw motion due to harsh environments with Hs = 4,0 meters and T = 7,7 sec are 0,615 m/m; 9,354x10-7 m/m; 1,048 m/m; 18,423x10-6 0/m; 2,225 0/m; and 12,671x10-8 0/m. It means that the amplitude response will always be smaller than the wave amplitude coming up. Another thing happened when using SLFR has longer frequency about 0,207 rad/sec than without using SLFR. Taking into RAO motion calculation, the fatigue life on catenary mooring systems for head seas are 412 years in mooring line 4 and mooring line 5 with using SLFR while without using SLFR for 6.636 years in mooring line 5. The structure is still in safe condition because of the design safety factor about 300 years.